RETHINKING THE THEORY OF TOURISM: WHAT IS TOURISM SYSTEM IN THEORETICAL AND EMPIRICAL PERSPECTIVE? - Wiweka, Kadek; Arcana, Komang Trisna Pratiwi (Institut Pariwisata dan Bisnis Internasional, 2019)
Tourism within the practical scope has gone beyond the development of tourism theory itself. Considering the importance of theory as a foundation for knowledge and understanding of a phenomenon, especially in the scope of tourism. Therefore this study attempts to fill the gap between the tourism theory that has been built with the latest empirical facts. In developing tourism theory, this research used the creation of theory approach. Where in the process, the creation of theory is more inductive (or can be regarded as a qualitative approach). The result of this research is that tourism as a system consists of two kinds of sub-system that is internal and external sub-system. The internal sub-system is the interaction between person or the tourist termed as the tourist demand, from the tourist generating region and during a trip to a destination called the tourism supply, linked by the intermediaries elements, to return to its original territory. While external sub-system consists of international trade factors, safety and security factors, natural or climate factors, social-cultural factors, technological factors, economic or finance factors, political factors, demographic, and geographical factors. The relationship between the internal and external sub-systems not only determined the existence of tourism, but otherwise the existence of tourism can also affect the two sub-systems (internal and external). The interesting thing about this research is that the phenomenon of tourism can be ‘limited’ by its own point of view which is described through a comprehensive and integrated system.